La transversalidad de género como innovación política de gobierno / The Transversality of Gender as Political Innovation of Government - Levin, Silvia (Impacto Científico, 2020)
RESUMENSe describe el enfoque que instalan las políticas transversales de igualdadde género como estrategias públicas de gobernanza, y las connotaciones innovadoras que trasladan a las relaciones entre Estado y sociedad y entre ciudadanos y ciudadanas en Argentina en el marco de América Latina.ABSTRACTThis paper describes the approach installed by the transversal politics ofequality of gender as public strategies of governance and the ninnovative connotations that translate the relationships between the State and society and between citizens in Argentina in the Latin American context